Systems of social protection and the Public System of Social Assistance - SUAS: analysis of a system under construction (Emancipação, 2025)
This article presents one of the innovatory forms of analysis the systems of social protection that recently appeared in the international literature. Subsequently, that discussion will be articulated with the dynamic of the structuring of the Brazilian system of social protection, in special the Public  System of Social Assistance - SUAS. This system is inserted in a path  dependency, which influence the Brazilian system of social protection, giving  those certain characteristics and specificities. Finally, this article aims to  establish parallels with the introduction of the SUAS in the regions North, Northwest, Valleys of the Jequitinhonha and Mucuri of the state of Minas Gerais.
Keywords: Social safety. Social assistance. Public system of social assistance. SUAS.